Clinical Outcomes for Severe COVID-19 Patients with Comorbid Type 2 DM through Dexamethasone Therapy at RSUP Dr. Sardjito Yogyakarta - Dewi, Novia Ariani; Andayani, Tri Murti; Trisnawati, Ika (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Background: Dexamethasone is a recommended therapy for severe COVID-19 patients who require hospital treatment. However, its use can affect blood glucose levels in patients, especially patients with diabetes mellitus comorbidity.Objectives: This study aims to determine the clinical outcomes for type 2 diabetes mellitus (DM) patients with Severe COVID-19 comorbidity through dexamethasone as COVID-19 therapy.Methods: This study employed the retrospective cohort an analytical observational research approach. Involving 60 patients as subjects, patients over the age of 18 received dexamethasone at RSUP Dr. Sardjito Yogyakarta between June 2021 and March 2022 and whose RT-PCR results showed severe COVID-19 with comorbidity of type 2 DM were included in the study. The blood glucose profiles derived from the patient's medical record data were the clinical outcome that already checked. The paired t-test was performed to analyze how dexamethasone affected the clinical results of the blood glucose profile.Results: The findings of the study were identified after using dexamethasone for four days, which showed that 78.30% of patients had an increased in blood glucose. Pre and post treatment of dexamethasone for four days had a significant impact on the patient’s blood glucose levels in this study, with an average change in blood glucose levels is 78.32 ± 116.77 (p<0.05).Conclusion: Dexamethasone therapy demonstrates a significant effect on blood glucose levels, resulting in a statistically difference between pre and post values for four days in patients with severe COVID-19 with type 2 DM comorbidity. Consequently, special monitoring needs to be carried out in severe COVID-19 patients with type 2 DM who receive dexamethasone to avoid worsening of the patient’s clinical condition.